Vortex dynamics in case of possible room temperature superconductivity - (:unkn) unknown (AMER INST PHYSICS, 2007)
Two-dimensional temperature dependent vortex dynamics has been studied by Monte-Carlo method. At low temperatures far below T-C, well known phase transition from glassy state to vortex liquid state known as melting has been obtained. Assuming the possible future existence of real high temperature superconductivity, the simulations extended to the range of room temperature. There, vortex state has shown a possible second phase transition analogous to gas state where vortices behave totally independent of each other. Since mobility of vortices means dissipation, this poses a real challenge for future applications of room temperature superconductivity.
Keywords: superconductivity; vortex matter; phase transition